The Influence Of Work Culture And Organizational Climate On The Performance Of Employees Of Perumda Tirta Hidayah Bengkulu City - Muhammad Rizki Pratama Ritonga; Ratnawili Ratnawili (Journal of Indonesian Management, 2024)
This research aim to analyze the influence of work culture and organizational climate on employee performance. The Research conducted is of a quantitative nature and was carried out at Perumda Tirta Hidayah City of Bengkulu from December 2023 to completion. The study involved a total of 50 employees. Data collection was done through interviews and questionnaires. The data analysis techniques employed in research inclueded validity testing, reliability testing, classical assumption testing, multiple linear regression, coefficient of determination, and hypothesis testing. Based on the results of this research, it can be concluded that work culture has a positive and significant influence on the performance of employees at Perumda Tirta Hidayah City of Bengkulu. Organizational climate has a positive and significant influence on the performance of employees at Perumda Tirta Hidayah City Of Bengkulu. Work culture and organizational climate jointly have a positive and significant influence on the performance of employees at Perumda Tirta Hidayah City of Bengkulu.